Increasing Pretrial Releases and Reducing Felony Convictions for Defendants: implications for Desistance from Crime - Pratt, Travis C. (Canadian journal of criminology and criminal justice, 2020)
The bulk of the desistance literature has focused on social/contextual factors (marriage, employment, peers) and their criminogenic consequences. Less attention has been devoted to the role of criminal justice system involvement in the desistance process, and most of the existing research indicates that system involvement tends to inhibit or delay desistance from crime. One recent effort to combat that pattern was implemented with the Responsive Interventions for Change (RIC) Docket in Harris County, Texas, in 2016. The RIC Docket was intended to increase defendants' access to a pretrial release bond and to reduce rates of felony convictions, thus lowering the risk of disrupting important prosocial ties and avoiding potentially stigmatizing labels. In the present study, we use case processing data on rates of pretrial release and felony convictions from one year prior to (N = 6,792) and three years following (N = 12,152) the implementation of the RIC Docket. Results show that those processed through the RIC Docket were 24% more likely to have access to pretrial release and 45% less likely to have their cases result in a conviction. We conclude by discussing the importance of policy changes intended to reduce barriers to the successful desistance process for individuals involved in the justice system. (English)